'Creature of statute': Legal bureaucracy and the performance of professionalism in Johannesburg. (December 2022) - Bolt, Maxim
South Africa's Master of the High Court administers property inheritance. Described as a 'creature of statute', and staffed by legally trained officials, the law takes centre-stage. Focusing on Johannesburg, the Master's biggest and busiest branch, this article examines how law is performed in bureaucratic encounters, and how this shapes the everyday relations that make legal bureaucrats as middle-class professionals. Middle-class status is performed in the very enactment of a professional system, inflected by the racialised positioning of a new post-apartheid generation of largely black officials. Formal qualifications facilitate forms of distinction that maintain both prestige and everyday roles. Yet this is fraught. The Master and its administrators are positioned between post-apartheid potential and apartheid legal legacies; between transformation and a still racialised society; between professional ideal as legal bureaucrats and the career possibilities of a more lawyerly legal world.